2013
DOI: 10.1039/c2ra22233g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel dicationic basic ionic liquids and its catalytic activities for biodiesel production

Abstract: Biodiesel produced by transesterification of vegetable oils or animal fats is a potential alternative fuel to diesel, given the limited resources of fossil fuel and its environmental concerns. Three novel dicationic basic ionic liquids (DBILs) have been prepared for synthesis of biodiesel from soybean oil. Among them, 1, 2-bis (3-methylimidazolium-1-yl) ethylene imidazolide performed best and the yield of biodiesel reached 99.6%, which was related to the basicity and miscibility properties of the IL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 30 publications
(25 reference statements)
0
27
0
Order By: Relevance
“…18,44 We are aware of the fact that situation detected in MeOH solution could be different from the one occurring in the reaction mixtures. This colorimetric method has been applied by us and others, to assess the basicity of functionalised dicationic ILs.…”
Section: Resultsmentioning
confidence: 99%
“…18,44 We are aware of the fact that situation detected in MeOH solution could be different from the one occurring in the reaction mixtures. This colorimetric method has been applied by us and others, to assess the basicity of functionalised dicationic ILs.…”
Section: Resultsmentioning
confidence: 99%
“…The biodiesel produced by transesterification of vegetable oils or animal fats is a potential alternative fuel to diesel, given the limited resources of fossil fuels and its environmental concerns (Fan et al 2013). 1, 2-Bis(3-methylimidazolium-1-yl) ethylene imidazolide performed best for the synthesis of biodiesel from soybean oil, with a yield biodiesel of 99.6%, which was related to the basicity and miscibility properties of the IL.…”
Section: Conversion Of Biomass Into Biofuelsmentioning
confidence: 99%
“…Therefore, basic ionic liquids will be more effective than acidic ionic liquids in glycone production under moderate conditions. Recently, basic ionic liquids have been applied widely in organic reactions as a basic catalyst (Chen et al, 2008;Fan et al, 2013). In the researches, Meindelsma et al (Meindelsma et al, 2005) pointed out that ionic liquids can separate aromatic hydrocarbons from mixtures of aromatic and aliphatic hydrocarbons, and Sun and Shi (Sun and Shi, 2012) indicated that basic ionic liquids of the imidazole anion can separate acidic compounds.…”
Section: Introductionmentioning
confidence: 98%